Faktori, kas ietekmē Latvijas piena nozares konkurētspēju Baltijas valstīs - Ismonaliev, Fayzullo (Latvijas Universitāte, 2019)
This study presents competitiveness analysis and factors influencing on the competitiveness in Latvian dairy sector among the Baltic states. Gross domestic product, the number of population, demographics, trade balance, labour cost indicators of each country and numbers of manufacturers, the revenue of the sector and its growth rate, volume sold of goods and its growth rate, average volume sold per capita of products, an average price of milk and cream, an average price of yoghurt and curdled milk, an average price of cream cheese and cheese in the dairy sector of every Baltic state are compared between among them and has been commented by three experts: Inga Orlova ( representative of Ministry of Agriculture of Republic of Latvia), Roberts Gudermanis and Filips Talbergs ( representatives of Investment and Development Agency of Latvia). The results were analysed based on Porter`s five forces and highlighted relatively a low level of bargaining power of buyers, a low level of bargaining power of suppliers, a high level of threat of new entrants, a low level of threat of substitutes, a high level of rivalry among the competitors among the Baltic states which concluded as a low level of competitiveness of Latvian dairy sector among the Baltic states. The outcomes of these analyses were applied to SWOT analysis and results of qualitative analyses highlighted that a price factor is the most influencing factor on the competitiveness of the Latvian dairy sector among the Baltic states. Latvian dairy sector firms should consider increasing their price competitiveness by producing a larger amount of products at a lower price and use a significantly higher amount of raw milk available in Latvia to produce more products and at the same time to cut off resource-driven from the country, which lowers volume produced in the competing countries` firms.
Factors influencing competitiveness of Latvian dairy sector in Baltic countries
Keywords: Ekonomika; Competitiveness; Dairy sector; Baltic countries; factors influencing competitiveness; Porter`s five forces